ANOMALI GAYA BERAT DAN TATAAN TEKTONIK SEKITAR PERAIRAN LAUT BANDA DAN PULAU SERAM - Budi Setyanta; Imam Setiadi (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Bouguer and free air gravity anomalies  of the  Banda Sea and Seram Island are divided into southren, central and northern parts. Gravity analyses based on land measurement  combined  with ftee air anomaly data of the sea produce crust structure model which close related to rock composition and tectonic position.  Crust structure at Banda Sea is mainly composed of basaltic crust of  Banda Sea as a base and folded occurrence, collision with granitic crust border (Australian continent fragment  ?).  Banda Sea basaltic  crust is underlying volcanic sediment  Banda  Island, while granitic crust is underlying Pre-Tertiary sediment rock at Seram Island. Collision which happened since early Pliocene of two different crust has caused many things such as material from many sources in Seram Island mad melange  rock and thrust fault that appeared in the surface. Tectonic intensity has also caused some granitic crust borders to get fragmentation which reduces value of the anomaly. Further-more, it appears volcanic rock of  Banda Sea has caused gravity tectonic  toward equilibrium process basaltic  crust. This geodynamic crust   model has an implication  to geological Potency product, both in economic or disaster risk.Keywords: gravity, tectonic, evolution, geological potency